Comparison of oxidant and antioxidant status of Çoruh trout (Salmo coruhensis), anatolian trout (Salmo rizeensis) and rainbow trout (Oncorynchus mykiss) spermatozoa - Kutluyer, Filiz; Kocabaş, Mehmet; Eri?Şi?r, Mine; Benzer, Fulya (Ataturk Universitesi, 2018)
The aim of present study was to compare oxidant and antioxidant status of Çoruh trout (Salmo coruhensis), Anatolian trout (Salmo rizeensis) and rainbow trout (Oncorynchus mykiss) spermatozoa. Fish were obtained from Uzungöl. Enzymatic antioxidant activities (superoxide dismutase, catalase, glutathione peroxidase), glutathione and lipid peroxidation (malondialdehyde) were determined in spermatozoa of three trout species. Results indicated that catalase (23.36±0.36 K/g.protein), glutathione peroxidase (74.00±1.5 U/g.protein), glutathione (0.57±1.24 µmol/g.cell) and malondialdehyde levels (6.55±2.01 nmol/g cell) were highest levels in Anatolian trout (S. rizeensis) spermatozoa. In conclusion, differences among species caused alterations in the antioxidant and malondialdehyde levels. © 2016 Ataturk Universitesi. All rights reserved.
Keywords: Antioxidant Status; Oncorynchus mykiss; Oxidant; Salmo coruhensis; Salmo rizeensis; Spermatozoa